1972
DOI: 10.1007/bf01249672
|View full text |Cite
|
Sign up to set email alerts
|

Foamy virus serotypes 1 and 2 in rhesus monkey tissues

Abstract: The isolation and serologic identification by cross neutralization tests showed the presence of simian foamy virus serotypes 1 and 2 in primary rhesus monkey brain, spleen, and kidney cell cultures. The frequency of isolation of foamy viruses from brain and spleen cell cultures was 86 % and from kidney cell cultures it was 36%. In primary spleen cell cultures 50~ of the foamy virus isolates were type 2. Of the 14 animals from which foamy virus was isolated, only r demonstrated serum neutralizing antibody to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

1972
1972
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…In fact, SFVs of both serotype 1 and serotype 2 were isolated from different organs within the same monkey as well as from a single organ (8). AGMs were found to be typically infected with SFVs of serotype 2 and serotype 3, but SFV of serotype 1 was also seen (7)(8)(9). More recent molecular studies have also shown that although SFVs generally circulate within a host species, interspecies transmission can occur (10,11).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…In fact, SFVs of both serotype 1 and serotype 2 were isolated from different organs within the same monkey as well as from a single organ (8). AGMs were found to be typically infected with SFVs of serotype 2 and serotype 3, but SFV of serotype 1 was also seen (7)(8)(9). More recent molecular studies have also shown that although SFVs generally circulate within a host species, interspecies transmission can occur (10,11).…”
mentioning
confidence: 95%
“…Early results of virus isolation or antibody detection based upon neutralization serotyping showed that, although macaques generally harbor SFVs of serotype 1, viruses with serotype 2 were also present in some cases. In fact, SFVs of both serotype 1 and serotype 2 were isolated from different organs within the same monkey as well as from a single organ (8). AGMs were found to be typically infected with SFVs of serotype 2 and serotype 3, but SFV of serotype 1 was also seen (7)(8)(9).…”
mentioning
confidence: 99%
“…Simian FVs (SFVs) possess a broad cell tropism (20, 21, 29. 46), tissue tropism (1,13,15,21,22,33,34,43,45), and species tropism (2,19,21,23). In fact, cross-species infection of humans has been reported in handlers of SFV-infected primates (10,19,21,32,40,41).…”
mentioning
confidence: 99%
“…This animal's infection with type II FV also appears to have prevented infection by another type of FV as no type I virus or neutralizing antibodies appeared after it was given a large intravenous dose of type I FV. Simultaneous infection, however, with more than one type of FV has been documented to occur in rhesus [28,29], cynomolgous [18], and African green monkeys [41,42], Virus was much more frequently recovered from the leukocytes of experi mentally inoculated animals than from throat swab specimens. FV was also found in spleeen, thymus, lymph nodes, kidney, and brain as had been described in previous studies.…”
Section: Experimental Infectionmentioning
confidence: 99%
“…The highest dilution of serum showing three to four plus fixation was considered the antibody titer. Cross-neutralization tests among the FV types I, II and III were performed, as described by O'Brien and associates [28], on five throat and white cell isolates obtained over 3-to 4-week intervals and on two tissue isolates in order to identify the type of FV isolated. …”
Section: Methodsmentioning
confidence: 99%